Modifying a multidisciplinary method to address challenging behavior in nursing home residents with dementia to involve family caregivers - Tasseron-Dries, Petra E. M.; Smaling, Hanneke J. A.; van der Steen, Jenny T.; Achterberg, Wilco P. (Frontiers in Dementia, 2024)
Challenging behavior and pain are common in nursing home residents with dementia. Challenging behavior and pain can be related and are stressful for residents, family caregivers and healthcare professionals. The STA OP! method provides a step-by-step protocol to manage challenging behavior and pain in nursing home residents with dementia. However, this method does not include a prominent and active role for family caregivers.The STA OP! method was modified to include a role for family caregivers, in co-creation with family caregivers and healthcare professionals using elements of a realist approach. In separate meetings, two advisory groups comprised of family caregivers and professionals discussed ideas on how to involve family caregivers in STA OP!. Furthermore, barriers to involving family and possible solutions to overcome those barriers were discussed. Experts who had experience with the STA OP! method assessed the feasibility of the ideas in a nominal group technique meeting.Thirty-eight ideas emerged in the advisory groups. The two ideas that generated the most discussion were Inviting family for a multidisciplinary meeting, and Assessment of pain in collaboration with family caregivers. Eventually, twenty-one ideas and suggestions to overcome possible barriers were included in a manual for the training of healthcare professionals in the adapted method, now called STA OP! with family.Healthcare professionals and family caregivers collaborated well to shape the involvement of family caregivers in this method for managing challenging behavior and pain. The collected ideas supported by all involved resulted in a modified method: STA OP! with family and can now be tested in daily practice.